Peran Orang Tua Dalam Mempengaruhi Keputusan Investasi - Tan, Hendra; MN, Nuryasman (Jurnal Ekonomi, 2024)
The purpose of this research is is to determine the influence of parents' financial behavior, financial literacy, and financial behavior on investment decisions, as well as the role of financial literacy in mediating the influence of parents' financial behavior on investment decisions. This research gathers 297 samples of investors age from 18 to 45 that live in DKI Jakarta using online distribute questionnaires. In this research, quantitative method, cross sectional studies and purposive sampling method was used. The data was then analyzed with SmartPLS 4.0. The research results show that parents' financial behavior has a positive and significant effect on financial literacy. Parental financial behavior, financial literacy, and financial behavior have a positive and significant effect on investment decisions. Financial literacy positively and significantly mediates the influence of parents' financial behavior on investment decisions.